Evolution of the central safety factor during stabilized sawtooth instabilities at KSTAR. (16th November 2017) - Messmer, M.C.C.; Ko, J.; Chung, J.; Woo, M.H.; Lee, K.-D.; Jaspers, R.J.E.
Abstract: A motional Stark effect (MSE) diagnostic has recently been installed in the KSTAR tokamak. A difficulty faced at KSTAR and common to other MSE diagnostics is calibration of the system for absolute measurements. In this report we present our novel calibration routine and discuss first results, evaluating the evolution of the the central safety factor during sawtooth instabilities. The calibration scheme ensures that the bandpass filters typically used in MSE systems are aligned correctly and identifies and removes systematic offsets present in the measurement. This is verified by comparing the reconstructed safety factor profile against various discharges where the locations of rational q surfaces have been obtained from MHD markers. The calibration is applied to analyse the evolution of q 0 in a shot where the sawteeth are stabilized by neutral beam injection. Within the analysed sawtooth periods q 0 drops below unity during the quiescent phase and relaxes close to or slightly above unity at the sawtooth crash. This finding is in line with the classical Kadomtsev model of full magnetic reconnection and earlier findings at JET.